Analisis Sentimen Pembelajaran Daring Menggunakan Metode NaÃ¯ve Bayes, KNN, dan Decision Tree - Tobby Wiratama Putra; Agung Triayudi; Andrianingsih Andrianingsih (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2022)
Corona Virus Disease or better known as Corona Virus has attacked all corners of the world, including Indonesia. It has been almost +1 year that this virus is still attacking Indonesia and has an impact on various sectors, one of which is education. To contain the spread of the virus, the government has set an online education system. Many complaints were experienced by students, especially students who returned home, many of them experienced difficulties in accessing the internet, so many tasks to complete, and many more. The purpose of this study is to obtain the accuracy of the classification results based on the level of accuracy of the perceptions of students who use Twitter regarding the implementation of online lectures. In this research, the method used is Naive Bayes, KNN, and Decision Tree. The data used in this study is Twitter data by crawling data. From the results of this study, the Decision Tree method has a high value among other methods with an accuracy of 61.92%, precision of 73.63%, and recall of 11.42%.